ANTI-INFLAMMATORY EFFECT OF CLOPIDOGREL IN ATHEROSCLEROSIS - L. I. Buriachkovskaia; A. B. Sumarokov; I. A. Uchitel; E. M. Gupalo (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To analyze the literary and own data about clopidogrel influence on platelets during inflammation and to reveal particularities of its usage in ischemic heart disease (IHD) patients with active inflammation. Material and methods. The platelet morphology and a number of leukocyte-platelet aggregates (LTA) were investigated with scanning electron microscopy in 110 patients with stable angina pectoris of I-III functional class and 18 healthy volunteers. Spontaneous and ADP-induced platelet aggregation were assessed with laser aggregatometre manufactured by LLC “BIOLA”. Mean platelet volume (MPV) was estimated with the hematological analyzer . All investigations were performed in IHD patients before and after 2 months of clopidogrel treatment 75 mg a day. Results. IHD patients demonstrated appearance of LTA and big reticular platelets in the blood, increase in MPV and spontaneous aggregation. ADP-induced platelet aggregation was rarely increased probably due to acetylsalicylic acid therapy in all IHD patients. These platelet activity changes are connected with increased risk of thrombotic events and correlated with inflammation markers levels. After 2 months of clopidogrel treatment LTA number reduced in 4 times and big reticular platelets number decreased in 2.5 times as well as MPV and spontaneous aggregation achieved the normal ranges. Conclusion. Clopidogrel has not only antithrombotic effect but also can diminish platelets morphological and functional changes connected with inflammation.